Addressing ‘biodiversity naivety’ through project-based learning using iNaturalist - Niemiller, K. Denise Kendall; Davis, Mark A.; Niemiller, Matthew L. (Journal for Nature Conservation, 2021)
Conservation and education outreach programs often highlight charismatic species or species of economic or ecological importance. However, without appreciable connections to nature, the foundation necessary to empathize with these programs is insufficient. While many students are familiar with charismatic organisms, such as large mammals or sea turtles, there are countless other species of conservation concern that many students are entirely unaware of. As species loss is expedited, it is imperative to counter biodiversity naivety, particularly as public education and awareness are central to successful conservation efforts. The most impactful educational experiences foster direct engagement with biodiversity by students. We highlight the use of project-based learning to nurture student exposure and understanding of biodiversity in undergraduate- and graduate-level courses through the use of iNaturalist. In these courses, students were required to document observations from class field experiences as well as personal explorations. These projects transformed the learning of biodiversity from passive in nature to a meaningful and active process allowing students to connect with species observed while concurrently participating in citizen science initiatives. We share recommendations for successful implementation of iNaturalist projects by educators as well as challenges and issues based on our experiences.
Keywords: Biodiversity blindness; Biodiversity naivety; Citizen science; Community science; Education